Magic in the mix - Barrows, Annie (Bloomsbury, 2014)
Life seems to be back to normal for "newly twinned" sisters Miri and Molly until their magical house sends them on a new time-traveling adventure to the Civil War, where they must risk everything to save two unusual soldiers and come to terms with the emotional truth about Molly's past.